2023
DOI: 10.1093/ejendo/lvad138
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of dysglycaemia after treatment of monoclonal gammopathy of endocrine significance

Bonnie Grant,
Gowri Ratnayake,
Claire L Williams
et al.

Abstract: In very rare cases of monoclonal gammopathy, insulin-binding paraprotein can cause disabling hypoglycaemia. We report a 67-year-old man re-evaluated for hyperinsulinaemic hypoglycaemia that persisted despite distal pancreatectomy. He had no medical history of diabetes mellitus or autoimmune disease but was being monitored for an IgG kappa monoclonal gammopathy of undetermined significance. On glucose tolerance testing, hyperglycaemia occurred at 60 minutes (glucose 216mg/dL), and hypoglycaemia at 300 minutes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Landgren et al also examined the association between DM and MGUS and found no significant association [21]. Interestingly, a recently published case report described a case of hypoglycemia due to insulin-binding paraprotein that resolved following treatment with lenalidomide to deplete the plasma cell clone [22].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Landgren et al also examined the association between DM and MGUS and found no significant association [21]. Interestingly, a recently published case report described a case of hypoglycemia due to insulin-binding paraprotein that resolved following treatment with lenalidomide to deplete the plasma cell clone [22].…”
Section: Diabetes Mellitusmentioning
confidence: 99%